Information Potential and Representativeness of The First General Population Census Of 1897 in The Bessarab Province - Nataliia P. Gavriliuk (Publishing house "Sreda", 2023)
The article is devoted to the study of the practice of preparing and conducting the First General Population Census in 1897 on the territory of the Bessarabian province. The research area was not chosen by chance and is connected with the events of today, namely the practice of determining the language of communication and functioning on the territory of the Republic of Moldova. The relevance of the study is beyond doubt, since, to study the composition of the population, the dynamics of the population and national composition, the social picture of the region, primary sources and their analysis by contemporaries of the First General Census of the Russian Empire are used, which allows answering some provocative questions of modern historians and politicians. The identification of the subjects, methods and stages of the census makes it possible to clarify the specifics of this approach in relation to the Russian Empire, since the methods and technologies for conducting population censuses borrowed in Europe required revision and adjustment, taking into account the realities of the Russian Empire. One cannot but agree that the results of the census have many shortcomings, in particular, in terms of the ethnic composition of the population, social groups and categories, the language of communication, the occupations of the inhabitants of the Bessarabian province, which is explained by the very organization of the census, the lack of qualified personnel, insufficient funding, etc. d. But, at the same time, it must be taken into account that for their time these were the necessary data and indicators that subsequently made it possible to determine the policy of the central government on the ground and in particular with regard to Bessarabia - the territory of which for many years was under the control of the Ottoman Empire and around which geopolitical disputes.